Design and Development of the Excel Devan Organizer Make-Up Private Course Training Application - Rizky Nur Aliza; Raditya Galih Whendasmoro; Fauziyah Fauziyah (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2023)
In private course training, Makae-Up offers a variety of packagestraining courses so that customers can choose according to their wishes.training, namely non-formal education held outside of learningTraining school is to add insight or knowledgeto that learning where excel devan organizer is foundThe problem with the course training is the CEO (Chief Executive) scheduleOfficer) who clashed on the wedding schedule. from existing problemsbuilt Design and manufacture of information systems Private course trainingmake-up on excel devan organizer Android-based is expected to be able todeal with these problems. for the analysis method using Unfield Modeling Language (UML) and using the programming language Borland Delphi and Mysql as the database with the design and manufacture of a training information system for private make-up courses on Android-based excel devan organizer can be easier to use, accurate and integrated.